Cu0-catalysed 1, 3-dipolar cycloadditions of α-amino acid derived N, N-cyclic azomethine imines to ynones. Issue 24 (15th June 2017) - Mirnik, Jona; Pušavec Kirar, Eva; Ričko, Sebastijan; Grošelj, Uroš; Golobič, Amalija; Požgan, Franc; Štefane, Bogdan; Svete, Jurij
Abstract: A series of 20 CuAIAC reactions between eight 4-acylamino substituted pyrazolidine-3-one-1-azomethine imines and four terminal ynones were performed using Cu 0 as catalyst. The corresponding fluorescent cycloadducts were obtained in very high yields upon simple workup. Thus, Cu-metal turned out to be a better catalyst than Cu I in terms of yield and ease of isolation. Availability of azomethine imines, mild reaction conditions, and simple workup enable a "click" access to libraries of densely substituted 2, 3-dihydro-1 H, 5 H -pyrazolo[1, 2- a ]pyrazol-1-ones. Reactivity of differently substituted dipoles was evaluated experimentally and by quantum chemical methods (DFT). Graphical abstract: